2005
DOI: 10.1063/1.1894786
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb explosion of ammonia clusters induced by intense nanosecond laser at 532 and 1064nm: Wavelength dependence of the multicharged nitrogen ions

Abstract: The Coulomb explosion of ammonia clusters induced by nanosecond laser field with intensity in the range of 10(10)-10(12) W cm(-2) and wavelength of 532 and 1064 nm has been studied. N2+ and N3+ ions are the main multicharged ions at 532 nm, while He-like N5+ ion is the domain multicharged ion at 1064 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
5
22
0
Order By: Relevance
“…Longer wavelengths facilitate the production of higher stage multiple-charge ions, and the charge-state distribution is almost independent of laser intensity (above the threshold value). Similar results were observed with laser irradiation of (C 6 H 6 ) n and (NH 3 ) n clusters [17,18].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Longer wavelengths facilitate the production of higher stage multiple-charge ions, and the charge-state distribution is almost independent of laser intensity (above the threshold value). Similar results were observed with laser irradiation of (C 6 H 6 ) n and (NH 3 ) n clusters [17,18].…”
Section: Resultssupporting
confidence: 90%
“…However, we have observed multiple-charge ions with a nanosecond laser intensity as low as $10 9 -10 11 W/cm 2 when irradiating different clusters such as benzene, ammonia, acetone, hydrogen sulfide, and xenon. The theoretical models mentioned above cannot explain this behavior [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The trend of the mean electron energy is consistent with that of multiply charged ions intensity as shown in Figure 4, and this is an evidence to support our opinion that multiply charged ions are produced via electron impact ionization. Moreover, the similar phenomena were also observed in the Xe [24], NH 3 [25], C 2 H 5 OC 2 H 5 [16] and C 6 H 6 [15,26] clusters system.…”
Section: Discussionsupporting
confidence: 61%
“…Sharma and Wang et al observed the dependence of multiply charged ions on the laser wavelength in CH 3 I clusters, respectively. And Sharma attributed this phenomenon to the resonant state in the CH 3 I cluster, but they could not account for some of the aspects of the Coulomb explosion phenomenon observed at laser intensity of $10 9 W/cm 2 in several other molecular cluster systems at the same laser wavelength [24,25,27]. Wang et al attributed this phenomenon to the inverse bremsstrahlung heating efficiency, which is proportional to k 2 [10].…”
Section: Discussionmentioning
confidence: 99%
“…10,14 So far the exact mechanism of energy absorption by clusters at low intensity laser fields leading to multiple ionization and eventually to Coulomb explosion of the cluster is not known. Of late, Li and co-workers have attempted to understand this phenomenon and based on their studies, they proposed a three-stage cluster ionization mechanism [30][31][32] to explain different facets of the Coulomb explosion phenomenon. This mechanism suggests that the primary step for generation of multiply charged atomic ions is the initial multiphoton ionization of the molecules within the cluster.…”
Section: -11mentioning
confidence: 99%